EFFECT OF HUMAN AMNIOTIC MEMBRANE AND SALINE SOAKED GAUZE DRESSINGS ON QUANTITATIVE SURFACE BACTERIAL COUNT IN GRANULATING BURN WOUNDS - ARVINDER SINGH; R. K. KESWANI; KAROON AGARWAL; U. SABHARWAL (Indian Journal of Plastic Surgery)
In a comparative study carried out in 10 major burn patients with granulating wounds, it was found that amniotic membrane is in no way superior to simple saline soaked gauze dressings in either decreasing the bacterial count or preparing the granulating raw area for autogrofting.